Blue Shark Bycatch and Conservation Gaps in Indonesian and Eastern Indian Ocean Fisheries: A Systematic Review of Spatial Risk, Fisheries Pressure, and Management Evidence - Dewi Shinta Achmad (International Forum of Researchers and Lecturers, 2026)
Blue sharks (Prionace glauca) are among the most frequently encountered pelagic sharks in oceanic fisheries, yet their conservation risk remains unevenly understood in Indonesian and eastern Indian Ocean waters. This systematic literature review synthesizes evidence on spatial risk, fisheries pressure, bycatch exposure, biological vulnerability, and conservation gaps relevant to blue shark management. Following a systematic search and thematic extraction strategy, the review organized peer-reviewed studies into four evidence domains: spatial distribution and habitat suitability; longline fisheries interaction and bycatch exposure; biological vulnerability, mortality, and population-level risk; and conservation measures, monitoring, and governance gaps. The synthesis shows that blue shark risk is not reducible to species presence or catch frequency. Instead, risk emerges from dynamic overlap between environmentally structured habitat, pelagic longline effort, demographic vulnerability, uncertain post-release survival, and weak species-specific monitoring. Evidence from Indian Ocean and Indo-Western Pacific studies indicates important seasonal and demographic variation, but Indonesia-specific data remain limited. This gap constrains stock assessment, spatial planning, and evaluation of bycatch mitigation. Conservation measures are further weakened where static protected areas, incomplete observer coverage, and trade monitoring are not integrated with regional fisheries governance. The review concludes that blue shark conservation in Indonesian and eastern Indian Ocean fisheries requires a risk-based framework linking habitat modelling, CPUE standardization, observer and electronic monitoring, post-release mortality studies, gear mitigation, and transboundary management under regional fisheries organizations.